The Key To Operational Success: Analysis Of The Influence Of Work Motivation And Competence On Employee Performance At Surya Agung Jaya. Cv - Aurellia, Rara Puspita; Noviani, Hilda; Nurdiana, Editya (International Journal of Social Service and Research, 2024)
This study aims to analyze the influence of work motivation and competence on employee performance in Surya Agung Jaya. CV, a packaging and paper box printing company. This study uses a quantitative research method with a focus on work motivation, competence, and employee performance. Data collection was carried out through interviews and questionnaires, with a sample of 150 employees using the saturated sampling method. The results of the study show that work motivation and competence have a significant positive influence on employee performance in Surya Agung Jaya. CV. Findings show that increased motivation and competence can have an impact on improving employee performance in the company. In addition, the study showed that work motivation directly affects employee performance, with higher levels of motivation correlated with improved performance. Based on the results of the research, recommendations for Surya Agung Jaya are proposed. CV as follows: implement strategies to increase employee work motivation, provide training and development programs to improve employee competencies, foster a culture of continuous learning and improvement in the organization, conduct regular performance evaluations, and encourage open channels of communication and feedback. This study offers a reference point for future researchers to develop these findings in their research and contribute to the theory and practice of employee performance development.